ADHOCISM PADA PERBEDAAN KONSEP SAYEMBARA ARSITEKTUR DENGAN HASIL AKHIR BANGUNAN, STUDI KASUS PADA 3 SAYEMBARA TERBANGUN - William Oscar Windoro, Chris; Saliya, Yuswadi (Jurnal Riset Arsitektur, 2025)
Abstract - Not all design concepts from architectural competitions are in accordance with the final results of the buildings being built. In this context, the theory of adhocism becomes relevant as an approach to understanding the changes and improvisations that occur in the process after the competition is over. This study aims to identify improvisation or change based on the Adhocism teory. The research method uses a qualitative descriptive method on 3 research objects. Data was collected through interviews with winners, and analysis regarding differences in contest bids and final results. Of the 3 study objects discussed, the design realization shows a significant difference. The design change factor in the realization of the building is due to design personalization or differences in design preferences between the project owner and the jury. case, has a tendency to occur the principle of "Re-personalizing subsystem," and "High Adhocism". Changes to the design of the contest evoked responses for a simple reason (High Adhocism), namely because the project owner has different preferences or tastes from the jury (Re-personalizing subsystem). This shows that there is a dynamic that occurs after judging, where the project owner has the freedom to influence the final outcome based on personal preferences. Keywords: adhocism, architecture competition, built architecture competition